Factors Influencing Health-Seeking Behavior Among Hypertensive Adolescents in the Working Area of Mungkid Public Health Center, Magelang Regency - Hafizha Ulya Nafiu; Dr. dr. Bagoes Widjanarko, MPH; Ratih Indraswari, SKM, M.Kes (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The detection of hypertension in adolescents presents a notable challenge due to its asymptomatic nature and infrequent identification during routine medical evaluations. According to a preliminary study conducted in the Health Department of Magelang Regency, hypertension has been identified as the most prevalent disease among the top 10 priority diseases in both 2020 (3,242 cases) and 2021 (1,904 cases). However, the proportion of patients who received healthcare services was only 7.3%. The objective of this investigation is to analyze the variables associated with the health-seeking behavior of hypertensive adolescents. The present investigation is a descriptive-analytical inquiry utilizing a cross-sectional research design. The study's sample comprises 171 participants drawn from the entire population of hypertensive adolescents aged between 14 and 24. The statistical analysis using chi-square indicates that there is a significant association between health-seeking behavior and various factors, including age category (p-value = 0.567), gender (p-value = 0.069), highest education level (p-value = 0.025), occupation (p-value = 0.399), family history of hypertension (p-value = 0.075), quality of health information (p-value = 0.013), knowledge of hypertension (p-value = 0.026), actions towards hypertension (p-value = 0.427), access to healthcare facilities (p-value = 0.000), availability of healthcare services and affordability (p-value = 0.002), and perception of individual needs regarding hypertension (p-value = 0.000).